Pulmonary Vein Index Is Associated With Early Prognosis of Surgical Treatment for Tetralogy of Fallot - Yuan, Haoyong; Qian, Tao; Huang, Ting; Yang, Hui; Huang, Can; Lu, Ting; Wu, Zhongshi (Frontiers in Pediatrics, 2021)
Objectives: To evaluate the predictive value of the pulmonary vein index (PVI) in the early prognosis of patients who received total tetralogy of Fallot (TOF) repair. Methods: We retrospectively reviewed 286 patients who underwent TOF repair in our institution between July 2013 and May 2020. The PVI, McGoon ratio, and Nakata index were measured and calculated. Logistic regression, linear stepwise regression, receiver operating characteristic (ROC) curve analysis, and Cox proportional hazards modeling were performed to evaluate the predictive value of PVI in the early prognosis after TOF repair surgery. Results: The median age and body weight were 1.23 (0.22-15.02) years and 9.00 (3.00-44.00) kg, respectively. There were 5 early deaths. The areas under the ROC curve for death were 0.89, 0.79, and 0.88 for the McGoon ratio, Nakata index, and PVI, respectively. A lower PVI better predicted prolonged postoperative hospital stay, cardiac intensive care unit stay, and ventilator time (Hazard Ratio, HR [95% Confidence intervals , CI]: 1.003 [1.002-1.004], p<0.001; 1.002 [1.001-1.004], p<0.001; 1.002 [1.001-1.003], p<0.001, respectively) and was a significant risk factor for high 24h max Vasoactive inotropic score (Crude Odds Ratio [OR] [95% CI]: -0.015 [-0.022, -0.007], p<0.001), serous effusion (Crude OR [95% CI]: 0.996 [0.992-0.999], p=0.020), delayed sternal closure (Crude OR [95% CI]: 0.983 [0.971-0.996], p=0.010), and the need for peritoneal dialysis (Crude OR [95% CI]: 0.988 [0.980-0.996], p=0.005). The area under the ROC curve of PVI for delayed postoperative recovery was 0.722 (p<0.001), and the estimated cutoff point was 300.3 mm2/m2. Conclusion: PVI is a good predictor of early prognosis for surgical treatment of TOF patients.